Temporal dynamics of the chicken mycobiome - Davies, Cary Pirone; Summers, Katie Lynn; Arfken, Ann M.; Darwish, Nadia; Chaudhari, Atul; Frey, Juli Foster; Schreier, Lori; Proszkowiec-Weglarz, Monika (Frontiers in Physiology, 2022)
The microbiome is an integral part of chicken health and can affect immunity, nutrient utilization, and performance. The role of bacterial microbiota members in host health is relatively well established, but less attention has been paid to fungal members of the gastrointestinal tract (GIT) community. However, human studies indicate that fungi play a critical role in health. Here, we described fungal communities, or mycobiomes, in both the lumen and mucosa of the chicken ileum and cecum from hatch through 14 days of age. We also assessed the effects of delayed access to feed immediately post-hatch (PH) on mycobiome composition, as PH feed delay is commonly associated with poor health performance. Chicken mycobiomes in each of the populations were distinct and changed over time. All mycobiomes were dominated by Gibberella, but Aspergillus, Cladosporium, Sarocladium, Meyerozyma, and Penicillium were also abundant. Relative abundances of some taxa differed significantly over time. In the cecal and ileal lumens, Penicillium was present in extremely low quantities or absent during days one and two and then increased over time. Meyerozyma and Wickerhamomyces also increased over time in luminal sites. In contrast, several highly abundant unclassified fungi decreased after days one and two, highlighting the need for improved understanding of fungal gut biology. Mycobiomes from chicks fed during the first two days PH versus those not fed during the first two days did not significantly differ, except during days one and two. Similarities observed among mycobiomes of fed and unfed chicks at later timepoints suggest that delays in PH feeding do not have long lasting effects on mycobiome composition. Together, these results provide a foundation for future mycobiome studies, and suggest that negative health and production impacts of delayed feeding are not likely related to the development of fungal populations in the GIT.